Policy driven and multi-agent based fault tolerance for Web services - 汤景凡 周波 何志均 (Journal of Zhejiang University. A. Science, 2005)
This paper proposes a policy driven and multi-agent based model to enhance the fault tolerance and recovery capabilities of Web services in distributed environment. The evaluation function of fault specifications and the corresponding handling mechanisms of the services are both defined in policies, which are expressed in XML. During the implementation of the services, the occurrences of faults are monitored by the service monitor agent through the local knowledge on the faults. Such local knowledge is dynamically generated by the service policy agent through querying and parsing the service policies from the service policies repository. When the fault occurs, the service process agent will focus on the process of fault handling and service recovery, which will be directed with the actions defined in the policies upon the specific conditions. Such a policy driven and multi-agent based fault handling approach can address the issues of flexibility, automation and availability.